Computational study of compressible flow through choke valve. (August 2022) - Mitra, Harsa; Gabel, Trevor; Williams, Dan; Koeck, Frank; Ostilla Mónico, Rodolfo; Alba, Kamran
Abstract: Failure of choke valves due to vortex shedding and flow-induced vibration (FIV) is common problem in industry. Mechanisms of head-on collision of fluid jets within a choke valve is investigated computationally in this manuscript. The benchmarked simulations are conducted at fixed flow rate and two different choke positions. The vorticity contours overlaid by velocity field are presented across various planes within the valve, shedding light on dynamics of the flow. The formation of a time-averaged four-lobed vortical structure is evident within the valve chamber. There is strong vortex shedding taking place along the tails of head-on colliding jets exhibiting unsteady flipping motion. Mach contours reveal choked flow condition upon constricted region of the valve ports. Pressure contours, accompanied by density graphs, uncover stagnation zone forming within the valve. Temperature profiles, on the other hand, detail significant gas cooling upon throttling due to Joule–Thomson effect. In order to extract dominant frequencies of vibration and corresponding Strouhal numbers, signal processing of transient pressure data at various probes inside the valve chamber has been performed through Fast-Fourier Transform (FFT), autocorrelation analysis, and continuous wavelet transform. At higher valve opening, spread-out dominant frequencies lie in the range < 5000 Hz. However, at lower opening (or valve flow coefficient) two distinct peaks approximately at 5000 Hz and 10, 000 Hz are visible from processed signals. Graphical abstract: Highlights: Studying fluid flow within a choke valve via industry-academia collaboration. Investigating two different choke positions at fixed flow rate using CFD. Quantifying vorticity, Mach number, pressure, temperature, and density. Studying underexpanded jets in a confined and non-quiescent medium. Signal processing of transient data, in both dimensional and dimensionless spaces.